<htm> Análise estatística interespecífica das espécies paranaenses (Brasil) de Plebeia (Apidae, Meliponini)</htm> - Joaquim Carlos Sena, Maia (Acta Biológica Paranaense, 2017)
<htm> Análise estatística interespecífica das espécies paranaenses (Brasil) de Plebeia (Apidae, Meliponini)</htm>